Atosiban interacts with growth hormones as adjuvants in frozen-thawed embryo transfer cycles - Chen, Haixiao; Cai, Jiali; Sun, Xiaohua; Liu, Lanlan; Liu, Zhenfang; Gao, Peng; Jiang, Xiaoming; Ren, Jianzhi (Frontiers in Endocrinology, 2024)
Objective: To investigate the interaction between atosiban and growth hormone (GH) as adjuvants in frozen-thawed embryo transfer (FET) cycles Method: A total of 11627 patients who underwent FET at Xiamen University Affiliated Chenggong Hospital between January 2018 to December 2022 were retrospectively analyzed. Among them, 482 patients received atosiban and 275 patients received GH. The interactions were estimated by comparing the odds ratio (OR) for pregnancy comparing patients with or without atosiban adjuvant in cohorts stratified according to the presence of GH use in either the overall cohort or a propensity score (PS) matched cohort. An interaction term (atosiban ⅹ GH) was introduced to a multivariate model to calculate the ratio of OR (ORR) adjusted for confounders.Results: For all patients receiving atosiban administration, no obvious effect on pregnancy was observed in comparison with either matched or unmatched controls. However, when the patients were stratified according to GH administration, atosiban showed a significant association with clinical pregnancy in comparison with either matched or unmatched controls among patients with GH treatment with rate ratios (RR) of 1.32 (95%CI: 1.05,1.67) and 1.35 (95%CI: 1,1.82), respectively. On the other hand, however, the association was absent among patients without GH treatment. The adjusted ORRs in both matched and unmatched cohorts were 2.44 (95%CI: 1.07,5.84) and 1.95 (95%CI: 1.05, 3.49) respectively.The combination use of atosiban and GH in FET cycles is potentially beneficial to the pregnancy. However, indications for the use of atosiban and GH may need further assessment.